(untitled) (Research, Society and Development, 2021)
This article was intended to investigate the actions taken by national and international institutions to guarantee the protection of children and adolescents in this moment of social isolation due to the Covid-19 pandemic. We carried out a quantitative research with the objective of analyzing the documentary proposals made by national and international institutions, such as UNICEF and Save the Children, and a qualitative research with four school principals from Elementary School 1 in the Municipal network of Caieiras - SP. We found that intersectoral work is important to guarantee the protection of children and adolescents, as well as to guarantee the right to technological access, which unfortunately is still precarious, especially with regard to the education scenario, requiring public policies that aim to protect and guarantee all rights of children and young people. To reflect on the theme of violence and the concept of a democratic State, we used the conceptions of researcher Marilena Chauí and sociologist Milton Santos.